Contribution A La Caractérisation Physico-Chimique Des Effluents De La Cosumar (Casablanca, Maroc) En Vue De Leur Traitement Approprié - Youssef, Errogui; Abdelmottalib, Nahli; Mohamed, Chlaida; Kamal, Chbihi (European Scientific Journal, ESJ, 2018)
The production process of the agro-food industry is aimed to ensure consumer’s solvency and satisfaction. As a result, these industries are accelerating their pace and rate of production by resorting to the intensive use of natural resources, especially water and energy. This production rate is accompanied by an increase in the volume of wastewater. According to the normative and legal requirements governing the protection of environment, this wastewater requires characterization in order to guide the choice of their treatment system and recovery. This paper focuses on the physicochemical characteristics of sugar agro-food industry wastewater (Cosumar-Morocco) in order to guide the choice of their appropriate treatment, allowing the reduction of their impacts and nuisances on the marine receiving environment or their reuse. The results obtained, following a follow-up of 4 months (March, April, May and June 2015), revealed that the industrial wastewater of Cosumar is relatively warm and basic with average values of temperature and pH respectively equal to 42, 71 ° C (± 2.61) and 9.38 (± 1.64). These liquid effluents also exhibit a high charge of oxidable matter (average COD=4801.33 mg.l-1 (±2342.66), organic matter (BOD5=3959.01 mg.l-1 ±2293.65), and particulate matter (average solids content = 275, 5mg.l-1±143.25). Moreover, the raw wastewater presents a strong mineralization, which is justified by an Electrical Conductivity of 6828.33 μs.cm-1 (±1704.44) and a Sulphate content of 94.33 mg.l-1 (± 31.66). The average concentrations of Kjeldahl Nitrogen and total Phosphorus are 6.5 mg.l-1 (± 2.54) and 0.67 mg.l-1 (±0.562) respectively. The COD/BOD5 ratio is 1.21, indicating the biodegradability of the wastewater produced, through which the biological treatment can be recommended.